Analysis on the natural gas distributed energy system scheme of a hospital complex in Xi'an. Issue 1 (March 2020) - Liu, Siyan; Kong, Qiongxiang; Liang, Nan; Li, Guoqing; Ma, Zhendi
Abstract: Natural gas distributed energy systems (NGDESs) have the advantages of peak load shifting and good economic benefits suitable situations, In the paper, the energy processes of NGDESs for large-scale hospitals in Xi'an are analyzed firstly, by considering the current policy of "grid-connected with no power injection" and the characteristics of prime mover, residual heat utilization equipment and energy consumption in hospital buildings. Secondly, the hourly cooling, heating and electrical loads of a hospital complex in one year are simulated by DesignBuilder software. Based on the further analysis of hourly loads in the year and its changes on typical days, the main devices of the NGDES are chosen optimally. The number of internal combustion engines is determined after comparing their economic benefits of different number of internal combustion engines. Finally, through comparing their initial investment and annual operating cost of the NGDES with that of the separating supply system, the results show that the annual average energy utilization rate of the NGDES is 80%, and its energy saving rate is 34.4% compared with that of the separating supply system.